The Role of Aquaculture and Fisheries in EU27 Food Security: A Comparative Analysis of EU13 and EU14 States - Alsaleh, Mohd; Abdul-Rahim, A. S. (Israeli Journal of Aquaculture - Bamidgeh, 2025)
Ocean-sourced foods are essential for providing food security, putting an end to starvation, and building healthy, environmentally friendly, and resilient food systems. Still, it is important to keep these in mind while discussing food. More money was made for developing countries by exporting blue foods than by exporting any other agricultural products combined. The European Union Region (EU27) has countries with diverse economic structures, from highly developed industrial economies in older members to those in Central and Eastern Europe still catching up. Splitting them allows for in-depth study of economic structures, models, and growth mechanisms, and can inform targeted policy recommendations for growth and convergence. The core objective of this study is to analyse how aquaculture and fisheries production impact food security in the EU2 members based on their economic structure development; European Union Developing State (EU13) and European Union Developed State (EU14) countries from 1990 to 2023. To address potential endogeneity issues, robust least squares (RLS), two-stage least squares (2SLS), and ordinary least squares (OLS) estimators were employed, leading to significant findings. The findings confirm the existing knowledge and indicate that the role of aquaculture and fisheries production in ensuring food security is more pronounced in developing EU13 countries compared to wealthier EU14 countries. Aligning with existing knowledge, the analysis reveals that factors such as gross domestic product (GDP) and governance play a more crucial role in ensuring sustainable food security in developing EU13 countries relative to their wealthier EU14 counterparts. The reliance on fossil fuels has a more pronounced impact on food insecurity in developed EU14 nations compared to developing EU13 countries. This study suggests that policymakers in the EU14 developed countries provide policies targeted at promoting the growth of aquaculture production and fisheries production top priority based on the research conclusions. Additionally, this study suggests that policymakers in the industrialized EU14 countries improve governance, aquaculture economics, fisheries economics, and the efficiency of fossil fuel usage.